WIND PROFILE VARIABILITY ANALYSIS FROM SODAR DATA IN SOUTH TANGERANG - Hilmi Mahmuda, Akhmad
South Tangerang has the potential for wind-related development but research on wind profiles in the area is still limited. Based on U.S. Energy Information Administration, it is shown that the demand for renewable energy is increasing by 30% every decade. The lack of research is a major problem in the development of the renewable energy sector. Using SODAR 2020-2022 data, this research focuses on the effect of land cover and wind direction on the wind profile for developing the potential of the energy sector from a meteorological aspect in South Tangerang and its surroundings. This study analyzes SODAR data which represents horizontal wind speed and direction. The wind direction data per 10 minutes is determined by the dominant wind direction – divided into four, Northeast, Southeast, Northwest and Southwest – from 20 to 200 meters altitude based on different land cover. Then, each cardinal direction that is averaged is a representation of the wind profile in the area where the wind comes from. This study analyzes all times, 00.00-06.00, 06.00-12.00, 12.00-18.00, 18.00-00.00, and each season (DJF, MAM, JJA, and SON). The results of this study show that the fastest wind profile over time for heights from 0 to 120 meters is found in the southeast wind. Then at an altitude of 120 to 200 meters, the fastest wind profile changes to southwest wind. The slowest wind profile is consistent with northwest winds. The wind profile is not sensitive to season because the wind profile for each season tends to be the same, showing no significant changes. In this study, land cover did not have much influence on the resulting wind profile because the areas with the highest settlement ratio did not produce the slowest wind profiles and the areas with the lowest settlement ratio did not consistently produce the fastest wind profiles